2004
DOI: 10.1111/j.1439-0272.2004.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article Male breast cancer - an andrological disease: risk factors and diagnosis

Abstract: Gynaecomastia, the enlargement of the male breast, is considered as an andrological disease. To date, a review on male breast cancer (MBC) has not been published in an andrological journal. The papers underlying this review were published from authors of different institutions: Clinical Genetics, Dermatology, Gynaecology, Internal Medicine, Oncology, Pathology, Psychiatry, Radiology and Surgery. MBC accounts for approximately 1% of breast cancer patients. A total of 182 men died of breast cancer in 1999, in Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 95 publications
0
14
0
2
Order By: Relevance
“…Men have a smaller amount of breast tissue than women but the same factors that influence malignant changes in women operate in much the same way in men. The incidence of MBC increases with age, flattening out after age 80 years, with a mean age at diagnosis of 63.4 years compared with 58.2 years in women [3]. Data from the National Cancer Institute Surveillance, Epidemiology and End Results (SEER) [4] showed that the incidence of MBC has been increasing for the last 30 years, from 0.86 per 100,000 to 1.08 per 100,000 [1].…”
Section: Epidemiologymentioning
confidence: 99%
“…Men have a smaller amount of breast tissue than women but the same factors that influence malignant changes in women operate in much the same way in men. The incidence of MBC increases with age, flattening out after age 80 years, with a mean age at diagnosis of 63.4 years compared with 58.2 years in women [3]. Data from the National Cancer Institute Surveillance, Epidemiology and End Results (SEER) [4] showed that the incidence of MBC has been increasing for the last 30 years, from 0.86 per 100,000 to 1.08 per 100,000 [1].…”
Section: Epidemiologymentioning
confidence: 99%
“…Data regarding male breast cancer have long been somewhat limited since results were mostly based on small samples. Recently, a number of studies investigated incidence and mortality trends for male patients compared to female patients [1,3,4] and reviewed the epidemiology and risk factors for male breast cancer [5][6][7][8][9][10][11][12][13][14]. Recent analyses in population-based surveys from the US confirmed several earlier findings: breast cancer occurs later in men than in women, with a higher stage, lower grade, and more oestrogen receptorpositive tumours [3].…”
Section: Introductionmentioning
confidence: 79%
“…2 Its prevalence may be as high as 40.5% in healthy men aged 18 -26 3 and 65% in hospitalized men aged 27-92. 5,6 An imbalance between estrogen and androgen seems to be the most important factor in the pathogenesis of gynecomastia. 5,6 An imbalance between estrogen and androgen seems to be the most important factor in the pathogenesis of gynecomastia.…”
Section: Discussionmentioning
confidence: 99%